2016
DOI: 10.1002/pc.24145
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal and hydrophobic surface properties of shape‐stabilized nanodiamond/fatty alcohol grafted poly(ethylene‐alt‐maleic anhydride) composite phase change materials

Abstract: Fatty alcohol grafted poly(ethylene‐alt‐maleic anhydride) (PEMA‐g‐FA) are synthesized from esterification of poly (ethylene‐alt‐maleic anhydride) (PEMA) with tetradecanol and octadecanol. Obtained PEMA‐g‐FA's composites were prepared with different ratios of nanodiamond as phase change materials (PCM).The chemical structure of the synthesized PEMA‐g‐FA was investigated by Fourier transform infrared spectroscopy. Phase change behaviors of PEMA‐g‐FA and their composites were examined by using differential scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Further research had shown that the organic segment on the organic/inorganic hybrid polymer is beneficial to improve the surface hydrophobicity of the material, thereby giving the surface of the phase change composite unique self‐cleaning performance (Figure 5A). Kahraman et al [88] . used myristyl alcohol, stearyl alcohol and polyglycolic anhydride (PEMA) as raw materials to synthesize fatty alcohol grafted polyglycolic anhydride (PEMA‐g‐FA).…”
Section: Hydrophobic Propertymentioning
confidence: 99%
“…Further research had shown that the organic segment on the organic/inorganic hybrid polymer is beneficial to improve the surface hydrophobicity of the material, thereby giving the surface of the phase change composite unique self‐cleaning performance (Figure 5A). Kahraman et al [88] . used myristyl alcohol, stearyl alcohol and polyglycolic anhydride (PEMA) as raw materials to synthesize fatty alcohol grafted polyglycolic anhydride (PEMA‐g‐FA).…”
Section: Hydrophobic Propertymentioning
confidence: 99%
“…Baştürk et al have developed shape stabilized poly(ethylene‐ alt ‐maelic anhydride) composites with nanodiamond as phase change material that exhibited enhanced surface properties, facilitating higher melting and freezing temperatures which are ideal for refrigeration and air conditioning systems . Ikada has explored polymer surface modification for medical appliances using grafting techniques 6c.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, for their enrollment as latent heat storage components they ought to have certain attractive, kinetic, thermodynamic, and chemical properties. Furthermore, easy access, availability and budget friendliness are also some of the facts, which should be considered .…”
Section: Introductionmentioning
confidence: 99%